Taxonomic clarification and neotype designation for three Indian xyleborine species (Coleoptera: Curculionidae, Scolytinae) - Smith, Sarah M.; Beaver, Roger A.; Singh, Sudhir; Cognato, Anthony I. (Zootaxa, 2018)
Xyleborini currently consists of more than 1168 species in 36 genera, nearly all of which were described in Xyleborus (Hulcr et al. 2015; Smith 2017). The tribe has been the focus of considerable taxonomic attention over the last decade resulting in phylogenetically based revisions and the erection of new genera (e.g. Hulcr et al. 2007, Hulcr and Cognato 2010). However in the Old World these efforts have largely been restricted to faunas of particular countries such as Taiwan (Beaver and Liu 2010), Thailand (Beaver et al. 2014), and Papua New Guinea (Hulcr and Cognato 2008). The region’s fauna was primarily described from the 1890s to the 1940s by three authors, W.F.H. Blandford, Hans Eggers and Karl Schedl. During the 1920s to the 1940s Eggers described numerous Xyleborus species from India and Myanmar (Burma), typically from single specimens or a small series, and deposited them in the Forest Research Institute (FRI) in Dehradun, Uttarakhand, India. Cotypes (paratypes), if present for the species, were kept in his collection. Upon his death, his collection was sent to the United States National Museum of Natural History but Schedl retained many of the types that are now at the Naturhistorisches Museum Wien (NHMW). In all, FRI houses 50 xyleborine holotypes, and most of these species are solely known from the holotype.